The use of the temporoparietal fascia flap in various clinical scenarios: A review of 71 cases - Nitin J Mokal; Amol N Ghalme; Deepak S Kothari; Mahinoor Desai (Indian Journal of Plastic Surgery)
Objective: This report details our experience with the use of the temporoparietal fascia flap in different scenarios of reconstruction and to discuss our technique of harvest, clinical applications, and review of literature of this versatile flap. Materials and Methods: A retrospective study of 82 cases of temporoparietal fascia flap in 71 patients, operated over a period of 10 years was conducted. Patients were grouped based on various clinical indications. The follow up period ranged from a minimum of 1 to a maximum of 10 years (Mean-four and a half years). All patients were analyzed for functional and aesthetic outcome using preoperative and postoperative photographs. Results: No significant complications were seen in our series. Only 2 out of 82 flaps had partial necrosis of flap (2.44%). Two patients who were operated for release of submucous fibrosis developed recurrence due to continued use of tobacco. The final outcome in one patient of ear reconstruction was unsatisfactory due to flap failure. The remaining patients had satisfactory functional and aesthetic outcomes (95.77%). None had other complications like temporal branch of facial nerve injury or alopecia along the scar line. Conclusion: The TPFF is one of the most reliable and versatile flap in the head and neck region. It can also be reliably used as free fascial flap. When its advantages are combined with the surgeon′s resourcefulness, various defects can be successfully reconstructed using the temporoparietal facia flap with satisfactory aesthetic and functional outcome.